Three-dimensional analysis of a tensile test on a propellant with digital volume correlation - Hild, F.; Fanget, A.; Adrien, J.; Maire, E.; Roux, S. (Archives of Mechanics, 2011)
A full three-dimensional study of a tensile test on a sample made of polymerbonded propellant is presented. The analysis combines different tools, namely, X-ray microtomography of an in situ experiment, image acquisition and treatment, 3D volume correlation to measure three-dimensional displacement fields. It allows for global and local strain analyses prior to and after the peak load. By studying the correlation residuals, it is also possible to analyze the damage activity during the experiment.